An efficient synthesis of 1α,25-dihydroxy-20-epi-vitamin D3 - Fraga, R. (2013)
The synthesis of 1,25-dihydroxy-20-epi-vitamin D3 (1) by Pd(0)-catalyzed coupling between the boronate ester (2) and the enol triflate (3) is described. This article is part of a Special Issue entitled ‘Vitamin D Workshop’.